Desempenho zootécnico, qualidade de ovos e avaliação econômica da inclusão do ácido guanidinoacético em rações de galinhas poedeiras - Jeniffer Godinho Ferreira Pimenta (2019)
The objective of this study was to evaluate the effects of dietary supplementation in laying hens' diets with guanidinoacetic acid (AGA) on the productive performance, egg quality and fortification and economic viability. A total of 720 101-week-old Lohmann LB-Lite® semi heavy layers were distributed in a completely randomized design, comprising five treatments defined by the AGA levels of the feed with six replications of 24 birds per experimental unit. The diets were formulated to contain 0.00, 0.05, 0.10, 0.15 and 0.20% AGA. Productive performance (feed intake, egg production, egg weight and mass, feed conversion per dozen and per egg mass, final weight of birds and viability) was assessed for 12 weeks. The quality (specific weight, weight and percentage of components, resistance and thickness of the shell, Haugh Units and color of the yolk) and the fortification of the eggs (creatine) were evaluated at four and 12 weeks after the inclusion of AGA. For economic viability, the average cost of inclusion per kg of AGA and the amount of feed per dozen eggs produced were used. The results were subjected to analysis of variance and polynomial regression of significant parameters was performed. During the experimental period, treatments did not influence the variables of feed intake, egg production, average weight and egg mass, feed conversion by egg mass and viability. For the final weight of the birds, a negative linear response was observed with the increase in AGA levels and the feed conversion per dozen had its optimal value determined by the quadratic regression model in 12 or 0.12% AGA. In the quality analyzes the treatments did not influence the variables of the percentage of the components (yolk, bark and albumen), resistance and thickness of the bark and the Haugh Units. After four weeks of AGA inclusion, the specific weight of the eggs responded linearly and positively and the color of the yolk had a quadratic response, with an optimum level of 0.12% AGA. In the 12th week of inclusion of AGA, the optimal level found for the color of the gem was 0.14% of inclusion of AGA. There was no effect of treatments on creatine fortification in eggs. In the economic analysis, a linear increase in the cost of the feed was observed together with the increasing increase of AGA in the feed. With the inclusion of 0.12%, the best feed cost per kg of 12 eggs produced was obtained. It is concluded that the inclusion of 0.12% AGA in commercial laying diets influenced parameters of performance and quality of eggs without strengthening the levels of creatine in eggs.